2004
DOI: 10.1177/0886260503259052
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Rejection Sensitivity in Childhood Sexual Abuse Survivors

Abstract: This study investigated whether interpersonal rejection sensitivity serves a mediating role between childhood sexual abuse (CSA) and three long-term psychological correlates of CSA in adult female survivors: depressive symptoms, anger suppression, and attenuated emotional expression. Interpersonal rejection sensitivity has been shown to be a risk factor for the development of depression and is elevated in CSA survivors. Similarly, attenuated emotional expression, particularly anger, has been related to adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 46 publications
5
38
2
Order By: Relevance
“…Contrary to previous studies such as Chapple et al (2005) research on physical neglect and Luterek et al (2004) findings on sexual abuse, respondents in this study who experienced physical neglect (2% of the sample) and sexual abuse (3% of the sample) were not found to endure social rejection by their peers. One possible explanation for this finding may result from the fact that only 2 and 3% of the respondents reported experiencing either of these two types of abuse.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Contrary to previous studies such as Chapple et al (2005) research on physical neglect and Luterek et al (2004) findings on sexual abuse, respondents in this study who experienced physical neglect (2% of the sample) and sexual abuse (3% of the sample) were not found to endure social rejection by their peers. One possible explanation for this finding may result from the fact that only 2 and 3% of the respondents reported experiencing either of these two types of abuse.…”
Section: Discussioncontrasting
confidence: 84%
“…With regard to child sexual abuse, a large array of studies reported short and long-term psychological and social negative consequences of child sexual abuse such as depression, (Whiffen et al 2000) poor self-esteem (Freshwater et al 2001;Johnson 2004), avoidance behavior (Bal et al 2003) and social and adjustment difficulties (DiLillo 2001;Rumstein-McKean and Hunsley 2001;Luterek et al 2004). Others focused on the relationship between childhood sexual abuse and dissociative disorders (e.g., Silberg 1998).…”
Section: Discussionmentioning
confidence: 97%
“…CSA survivors use emotional suppression and avoidance strategies (e.g., denial, wishful thinking, detachment) more generally (e.g., Batten, Follette, & Aban, 2001) and to cope with their abuse histories (Leitenberg, Greenwald, & Cado, 1992;Long & Jackson, 1993;Sigmon, Greene, Rohan, & Nichols, 1996). Finally, a CSA history has been shown to be related to anger suppression (Luterek, Harb, Heimberg, & Marx, 2004;Scott & Day, 1996) and attenuated emotional expressivity (Luterek et al, 2004) in adulthood.…”
mentioning
confidence: 94%
“…The cortisol awakening response has been positively associated with prior-day feelings of loneliness, sadness, threat, and lack of control, and negatively with same-day levels of fatigue, somatic symptoms (Adam et al, 2006), and positively with same-day number of positive social contacts (Stetler and Miller, 2005). It has been hypothesized that the awakening ARTICLE IN PRESS 2 Interestingly, childhood physical, and especially sexual abuse, appears to be more common among hypocortisolemic syndrome patients (Wessely et al, 1999), and rejection sensitivity mediated the relationship between childhood sexual abuse and later depressive symptoms (Luterek et al, 2004).…”
Section: Article In Pressmentioning
confidence: 99%